Programmed cell death ligand 1 expression on monocytes is inversely correlated with tumour response to preoperative chemoradiotherapy for locally advanced rectal cancer. (24th May 2022) - Tojo, Mineyuki; Horie, Hisanaga; Koinuma, Koji; Miyato, Hideyo; Tsukui, Hidenori; Kaneko, Yuki; Futoh, Yurie; Kimura, Yuki; Takahashi, Kazuya; Saito, Akira; Ohzawa, Hideyuki; Yamaguchi, Hironori; et al.
Abstract: Aim: The clinical efficacy of chemoradiotherapy (CRT) is largely dependent on host immune status. The aim of this study was to identify possible markers expressed on circulating mononuclear cells to predict tumour response in patients with locally advanced rectal cancer (LARC). Methods: Peripheral blood samples were obtained from 47 patients diagnosed with LARC before and after CRT. The numbers of lymphocytes and monocyte subsets were analysed using flow cytometry. Based on clinical and pathological findings, patients were classified as high or low responders. Results: Lymphocyte counts were markedly decreased after CRT. Total numbers of lymphocytes ( p  = 0.030) and CD4(+) T cells ( p  = 0.041) in post‐CRT samples were significantly lower in low responders than in high responders. In contrast, monocyte counts were not reduced and the number of CD14 dim (+) CD16(+) nonclassical (patrolling) monocytes were somewhat increased after CRT ( p  = 0.050). Moreover, the ratios of programmed cell death ligand 1 (PD‐L1) (+) cells on patrolling monocytes before and after CRT were significantly higher in low responders than in high responders ( p  = 0.0046, p  = 0.0006). The same trend was observed for classical and intermediate monocytes. The expression of PD‐L1 on patrolling monocytes before CRT correlated inversely with the number of T cells and natural killer (NK) cells after CRT. PD‐L1(+) ratio in patrolling monocytes was an independent predictor for response to CRT. Conclusion: Programmed cell death ligand 1 (PD‐L1) expression on patrolling monocytes suppresses cell‐mediated immunity in patients receiving CRT which could be related to tumour response, and may be a useful biomarker for decision‐making in the management of patients with LARC.